EXPLORING SPEECH ACTS IN PRESIDENT PRABOWO’S POLITICAL DISCOURSE: A QUALITATIVE STUDY BASED ON AUSTIN’S THEORY - Utep Sobali; Elis Chalisyah; Sudirman (JOLADU: Journal of Language Education, 2025)
This study explores the use of speech acts in President Prabowo Subianto’s SPIEF 2025 speech by applying Austin’s Speech Act Theory within a qualitative descriptive framework. The research aims to identify the types, frequency, and functions of speech acts, with a particular focus on commissive and expressive acts in relation to Indonesia’s domestic priorities and international diplomacy. The data were analyzed using Miles and Huberman’s Interactive Model (1994), which involves three stages: data reduction, data display, and conclusion drawing. Findings reveal that assertive acts dominate the speech, serving to establish credibility and frame Indonesia’s socio-economic context, while commissive acts highlight Prabowo’s commitments to food security, industrialization, and anti-corruption. Expressive acts, including gratitude, pride, and apologies, are strategically used to foster rapport and strengthen diplomatic relationships. The study concludes that Prabowo’s discourse integrates factual assertions, policy commitments, and emotional appeals to balance domestic development goals with global collaboration, demonstrating a rhetorical strategy that blends assertiveness with diplomacy.